2017
DOI: 10.1093/ofid/ofx239
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain: A Possible Side Effect of All Antiretrovirals

Abstract: Weight gain and body mass index (BMI) increase are central issues in patients living with HIV who need to minimize the risk of metabolic disease. Information collected through the SCOLTA cohort revealed significant 1-year BMI increase in patients treated with dolutegravir (P = .004), raltegravir (P = .0004), elvitegravir (P = .004), darunavir (P = .0006), and rilpivirine (P = .029). BMI gain correlated with low baseline BMI (P = .002) and older age (P = .0007) in Centers for Disease Control and Prevention stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 14 publications
4
52
0
7
Order By: Relevance
“…Several studies have reported an increasing prevalence of being overweight and obese in PWH, and have demonstrated that weight gain occurs in many PWH after initiating antiretroviral therapy (ART) [1][2][3][4]. Factors associated with weight gain in PWH include demographic factors (such as sex and race), HIV disease-related factors (such as disease stage and viral load), and ART-associated factors (specific antiretroviral drugs) [2,3,[5][6][7][8][9]. These observations have led to several non-exclusive mechanistic hypotheses for ART-associated weight gain, including a mirroring of societal trends, a return-to-health effect of ART, improved tolerability of ART regimens, and off-target effects of antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increasing prevalence of being overweight and obese in PWH, and have demonstrated that weight gain occurs in many PWH after initiating antiretroviral therapy (ART) [1][2][3][4]. Factors associated with weight gain in PWH include demographic factors (such as sex and race), HIV disease-related factors (such as disease stage and viral load), and ART-associated factors (specific antiretroviral drugs) [2,3,[5][6][7][8][9]. These observations have led to several non-exclusive mechanistic hypotheses for ART-associated weight gain, including a mirroring of societal trends, a return-to-health effect of ART, improved tolerability of ART regimens, and off-target effects of antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight/obesity has become more common [4,5]. Some experts considered this shi of HIV/AIDS clinical picture or the weight gain among PLWH as a side e ect of all ART regimens [6], while for others, it was considered to be an immunological response or a re ection of an increased CD4 cell count [7]. is is because of the substantial number of reports of associations between CD4 cell increase and weight gain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A discussion is currently ongoing about the role of integrase inhibitors in weight gain. Some authors report a significant weight gain in patients starting this class (15,16), although a similar effect could be observed in other classes (17), with differences existing between drugs from the same class. The effectiveness of cohort drugs in naïve patients, at least during the first year of treatment, was comparable.…”
Section: Discussionmentioning
confidence: 65%